Gestión de residuos sólidos peligrosos durante la generación de energía eléctrica en la central térmica de Requena – 2018 - Torres Diaz, Heber Jair (2023)
The work was developed in Requena, located to the right margin of the river Ucayali, the objective was to diagnose the administration of dangerous solid residuals during the electric power generation. The design was Not parametric of qualitative-quantitative type. The population was 38 people; to determine the dependability a semi-structured record it was elaborated and he/she underwent it the test of Alfacronbach-1, with 0.5% of probability, being concluded that, in the month of July among solid residuals, semisolids and liquids originated the biggest quantity (140 and 1900 kg/day), the house forces it is the area that generates bigger quantity of these residuals (63 and 470 kg), with respect to the activity this same area generates (52 and 680 kg), according to the danger of it lauds materials that the sawdust is used it occupies the first place with 40 kg of solid residuals and the oils used with 610 kg they represent the highest generation in this month, it is necessary to keep in mind that this month is festival for the native anniversary and the energy demand is bigger for the increment of the commercial and festival activities, regarding the knowledge on the handling of dangerous residuals and the Norma Peruvian Technique 900.058:2005 all say to know it, for what the hypothesis is accepted; since this diagnosis helped to make decisions more guessed right with respect to the handling of these dangerous residuals that you/they are generated.